KESANTUNAN TINDAKTUTUR DIREKTIF DALAM NOVEL TERJEMAHAN HARRY POTTER TAHUN 1 DAN 2 KARYA J. K. ROWLING SERTA RELEVANSINYA SEBAGAI BAHAN AJAR DI SMP - Agus Sriyatmoko; Purwadi Purwadi; Raheni Suhita (Universitas Sebelas Maret, 2018)
The purpose of this study is to describe (1) the form of directive speech acts in JK Rowling's Harry Potter novels year 1 and 2, (2) the form of language politeness, (3) the relevance of the Harry Potter novelsyear 1 and 2 in Indonesian language learning to students in middle school. The data collection technique used in this study was purposive sampling and data analysis used an interactive analysis model. The results of this study indicate that the form of directive speech acts and compliance with the principles of politeness contained in the Harry Potter novels year 1 and 2 by J. Rowling are as follows: (1) speech acts; requests, questions, rules, prohibitions, granting permits, and directive forms of counseling which numbered 419 data; (2) compliance with the principles of teacher and student politeness during the learning process is found as many as 118 data; (3) Harry Potter novels year 1 and 2 by J. K. Rowling are related to literary learning in junior high schools.